1991
DOI: 10.1093/oxfordjournals.aje.a115871
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Long-term Recall of Participation in Physical Activity by Middle-aged Men and Women

Abstract: The reliability of long-term recall of physical activity participation was examined in 322 women and 129 men in a worksite health study conducted at the Liberty Corporation, Greenville, South Carolina during 1976-1987. Leisure time physical activity was assessed at baseline; and energy expenditure in total, light, moderate, and vigorous activities was calculated. The long-term recall of baseline activities was determined 1-10 years after the examination. The relation between actual baseline and recalled activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 0 publications
5
64
2
Order By: Relevance
“…The corresponding average reproducibility values for the 6 remaining items were 0.63 for 2 weeks and 0.43 for 6 years. The results are in accordance with the previously reported results, with comparisons of different time intervals between test and re-test (1 I), and also with the results of a study of physical activities during leisure time (15). The majority of the subjects in our study (about 75%) were still working in the same occupations in 1995 as in 1989.…”
Section: Discussionsupporting
confidence: 93%
“…The corresponding average reproducibility values for the 6 remaining items were 0.63 for 2 weeks and 0.43 for 6 years. The results are in accordance with the previously reported results, with comparisons of different time intervals between test and re-test (1 I), and also with the results of a study of physical activities during leisure time (15). The majority of the subjects in our study (about 75%) were still working in the same occupations in 1995 as in 1989.…”
Section: Discussionsupporting
confidence: 93%
“…Interviewer-derived assessments of lifetime physical activity have been observed to be reproducible (Friedenreich et al, 1998a) and to provide reasonable recall accuracy for periods of 2 (Slattery and Jacobs, 1995) to 10 years (Blair et al, 1991). Reporting errors in historical activity patterns would appear to be more problematic for the quantitative aspects (i.e., frequency, intensity, duration of activity), but less so for the dichotomous assessment of exercise (i.e., yes/no) as used in the present study.…”
mentioning
confidence: 68%
“…That approach introduces a concern relating to recall bias, and it is unclear whether the reports of smoking and pa outcomes overestimated or underestimated the true values. Studies addressing the issue have found that recall of past pa behaviour up to 30 years into the past is generally reliable, but accuracy of recall for the rigour of the activity can vary [54][55][56] . An analogous study examining recall in smoking data indicated that, although 20-year recall was reliable for smoking status, recollection of smoking amounts were less reliable 57 .…”
Section: Discussionmentioning
confidence: 99%